More on unemployment and vacancy fluctuations - Dale T. Mortensen; Éva Nagypál (Institute for the Study of Labor (IZA), 2005)
Shimer (2005a) argues that the Mortensen-Pissarides equilibrium search model of unemployment explains only about 10% of the response in the job-finding rate to an aggregate productivity shock. Some of the recent papers inspired by his critique are reviewed and commented on here. Specifically, we suggest that the sole problem is neither the procyclicality of the wage nor the failure to account fully for the opportunity cost of employment. Although an amended version of the model, one that accounts for capital costs and counter cyclic involuntary separations, does much better, it still explains only 40% of the observed volatility of the job-finding rate. Finally, allowing for on-the-job search does not improve the amended model's implications for the amplification of productivity shocks.
Keywords: 330; labor market search; unemployment and vacancies volatility; job-finding rate; productivity shocks; Theorie der Arbeitslosigkeit; Arbeitsuche; Theorie